The Practice of Unsolicited Goods in TikTok Shop COD Transactions: A Review of Positive Law and Islamic Law - Naufal Farrel Himawan; Muthoifin (Seutia Hukamaa Cendekia, 2026)
This study analyzes the practice of unsolicited goods in Cash on Delivery (COD) transactions on the TikTok Shop platform, focusing on dispute resolution methods for such cases. This issue reflects the inconvenience consumers face in e-commerce transactions. This study aims to provide a thorough overview of legal protections for consumers in unsolicited goods transactions conducted via COD without the consumer's consent or through fictitious orders. This research employs a normative method, using a literature review and interviews with consumers currently experiencing cases of unsolicited goods. The study finds that unsolicited goods delivered through COD transactions violate consumer rights because consumers are compelled to accept and pay for goods they never ordered. Under Indonesian positive law, such practices conflict with Law No. 8 of 1999 on Consumer Protection, Government Regulation No. 80 of 2019 on Electronic Commerce, and regulations concerning electronic information and personal data protection. In Islamic law, the practice is invalid because it lacks mutual consent (ridha), contains elements of gharar and tadlis, and may be classified as an akad fudhuli, which is not binding without the consumer's approval. The study also shows that liability is shared among sellers, platforms, and, to a limited extent, couriers, although platforms may bear stronger responsibility due to their role as transaction facilitators. This research concludes that stronger regulation, platform supervision, consumer education, and digital literacy are needed to ensure legal certainty and protect consumers from unsolicited goods in COD transactions.